Roles of NF-κB in Cancer and Their Therapeutic Approaches - Véronique Baud (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Although mortality rates have declined in recent years, the majority of cancers are still difficult to treat and the medical need for better cancer treatment is evident. The current anticancer armamentarium includes many active agents that are applied across tumor types. However, most of these broadly-active anticancer drugs have a small therapeutic index and barely discriminate between malignant and normal cells. In recent years the focus has shifted to the development of rationally designed, molecularly-targeted therapy for the treatment of a specific cancer, therefore offering the promise of greater specificity coupled with reduced systemic toxicity. NF-kB transcription factor family as emerged as such a promising target for cancer therapy. This Special Issue will explore the routes from NF-kB basic research, cancer research and oncogenomics into the development of NF-kB-based cancer therapeutics and biomarkers. We invite research and review papers in any area of the NF-kB field that are related, but not limited to, fundamental understanding of NF-kB signaling pathways, gene expression profiling, epigenetic regulation, diagnostic, prognostic and pharmacogenomic biomarkers, molecular targets driving the progression of human cancers, cancer drug development on these targets, clinical trial with new agents, and validation in animal models. We hope that this Special Issue reflects the exciting era that we are living in with respect to the field of NF-kB and its applications in cancer research.